Cinnamic acid alleviates endothelial dysfunction and oxidative stress by targeting PPARδ in obesity and diabetes - Yizhen Bai; Dechao Tan; Qiaowen Deng; Lingchao Miao; Yuehan Wang; Yan Zhou; Yifan Yang; Shengpeng Wang; Chi Teng Vong; Wai San Cheang (Chinese Medicine)
Abstract Objective Cinnamic acid (CA) is a bioactive compound isolated from cinnamon. It has been demonstrated to ameliorate inflammation and metabolic diseases, which are associated with endothelial dysfunction. This study was aimed to study the potential protective effects of CA against diabetes-associated endothelial dysfunction and its underlying mechanisms. Methods High-fat diet (HFD) with 60 kcal% fat was used to induce obesity/diabetes in C57BL/6 mice for 12 weeks. These diet-induced obese (DIO) mice were orally administered with CA at 20 or 40 mg/kg/day, pioglitazone (PIO) at 20 mg/kg/day or same volume of vehicle during the last 4 weeks. Isolated mouse aortic segments and primary culture rat aortic endothelial cells (RAECs) were induced with high glucose (HG) to mimic hyperglycemia and co-treated with different concentrations of CA. Results In DIO mice, four-week administration of CA, particularly at 40 mg/kg/day, diminished the body weights, blood pressure, fasting blood glucose and plasma lipid levels, and ameliorated endothelium-dependent relaxations (EDRs) and oxidative stress in aortas. The beneficial effects of CA were comparable to the positive control group, PIO. Western blotting results indicated that CA treatment upregulated the expression of peroxisome proliferator-activated receptor delta (PPARδ), and activated nuclear factor erythroid 2-related factor 2 (Nrf2)/ heme oxygenase-1 (HO-1) and AMP-activated protein kinase (AMPK)/ protein kinase B (Akt)/ endothelial nitric oxide synthase (eNOS) signaling pathways in mouse aortas in vivo and ex vivo. HG stimulation impaired EDRs in mouse aortas and inhibited nitric oxide (NO) production but elevated reactive oxygen species (ROS) levels in RAECs. CA reversed these impairments. Importantly, PPARδ antagonist GSK0660 abolished the vasoprotective effects of CA. Molecular docking analysis suggested a high likelihood of mutual binding between CA and PPARδ. Conclusion CA protects against endothelial dysfunction and oxidative stress in diabetes and obesity by targeting PPARδ through Nrf2/HO-1 and Akt/eNOS signaling pathways.